Noradrenaline is crucial for the substantia nigra dopaminergic cell maintenance. (December 2019) - af Bjerkén, Sara; Stenmark Persson, Rasmus; Barkander, Anna; Karalija, Nina; Pelegrina-Hidalgo, Noelia; Gerhardt, Greg A.; Virel, Ana; Strömberg, Ingrid
Abstract: In Parkinson's disease, degeneration of substantia nigra dopaminergic neurons is accompanied by damage on other neuronal systems. A severe denervation is for example seen in the locus coerulean noradrenergic system. Little is known about the relation between noradrenergic and dopaminergic degeneration, and the effects of noradrenergic denervation on the function of the dopaminergic neurons of substantia nigra are not fully understood. In this study, N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine (DSP4) was injected in rats, whereafter behavior, striatal KCl-evoked dopamine and glutamate releases, and immunohistochemistry were monitored at 3 days, 3 months, and 6 months. Quantification of dopamine-beta-hydroxylase-immunoreactive nerve fiber density in the cortex revealed a tendency towards nerve fiber regeneration at 6 months. To sustain a stable noradrenergic denervation throughout the experimental timeline, the animals in the 6-month time point received an additional DSP4 injection (2 months after the first injection). Behavioral examinations utilizing rotarod revealed that DSP4 reduced the time spent on the rotarod at 3 but not at 6 months. KCl-evoked dopamine release was significantly increased at 3 days and 3 months, while the concentrations were normalized at 6 months. DSP4 treatment prolonged both time for onset and reuptake of dopamine release over time. The dopamine degeneration was confirmed by unbiased stereology, demonstrating significant loss of tyrosine hydroxylase-immunoreactive neurons in the substantia nigra. Furthermore, striatal glutamate release was decreased after DSP4. In regards of neuroinflammation, reactive microglia were found over the substantia nigra after DSP4 treatment. In conclusion, long-term noradrenergic denervation reduces the number of dopaminergic neurons in the substantia nigra and affects the functionality of the nigrostriatal system. Thus, locus coeruleus is important for maintenance of nigral dopaminergic neurons. Highlights: Repeated DSP4 administration produces a stable cortical noradrenergic denervation. Noradrenergic denervation affects the functionality of the nigrostriatal system. Long-term noradrenergic denervation reduces the nigral dopaminergic neurons.